Fetal neurobehavior assessed by three-dimensional/four-dimensional sonography - Kurjak, Asim (Zdravniški vestnik, 2010)
Recent development of three-dimensional (3D) and four-dimensional ultrasound (4D) provided us with new possibilities to study fetal movements and behavior.Many studies have been conducted in order to provide information on specific movement patterns in normal and highrisk fetuses. This was the base for a multicenter study on the use of new scoring system for fetal neurobehavior the purpose of which is to recognize fetuses at increased risk for a poor neurological outcome.The purpose of this paper is to give a brief reviw on the use of 3D and 4D ultrasound in the assessment of fetal behavior.
Keywords: Behavior; Dejavniki tveganja; Fetal Movement; gibanje; human pregnancy; Neurologic Examination; neurology; nevrologija; Nevrološka preiskava; nosečnost; Nosečnost, visoko rizična; plod; Plod, gibanje; Pregnancy, High-Risk; Risk Factors; ultrasonografija; Ultrasonografija predrojstvena; Ultrasonography, Prenatal; Vedenje